MEASUREMENT OF DIFFERENT COMPONENTS OF SECONDARY RADIATION ONBOARD INTERNATIONAL SPACE STATION BY MEANS OF PASSIVE DETECTORS - Inozemtsev, K O; Kushin, V V; Strádi, A; Ambrožová, I; Kodaira, S; Szabó, J; Tolochek, R V; Shurshakov, V A (Radiation protection dosimetry, 2018)
The evaluation of different components of secondary radiation (charged fragments and neutrons) onboard ISS is described. Solid-state nuclear track detectors CR-39™ were applied for the measurements of short-range nuclear fragments, while the measurements of neutrons were carried out by means of thermo-luminescent dosimeters with various concentrations of 6Li and 7Li. The flux of charged secondaries and the gamma-equivalent neutron dose are presented in function of the low-LET dose in various modules of the Russian segment of ISS.
Keywords: kosmická loď; dávka záření; Occupational Exposure; Neutrons; kosmonauti; neutrony; termoluminiscenční dozimetrie; pracovní expozice; Spacecraft; radiometrie; kosmické záření; Astronauts; Cosmic Radiation; Radiation Dosage; lidé; Thermoluminescent Dosimetry; Humans; Radiometry; monitorování radiace; Radiation Monitoring